Prevention of Food Fraud in Egypt: Policy Implementation Challenges and The Way Forward - Shalaby, Hager Yehia (AUC Knowledge Fountain, 2024)
Prevention and control of food fraud is now an emerging policy goal for different governments. Food fraud is intentionally adulterating food intended for personal gain and deceiving consumers. Adulterated food continues to be a significant threat to Egypt's food sector because of its negative impact on the food industry's reputation. Additionally, it jeopardizes the success of initiatives to increase investment, tourism, and exports in Egypt. Addressing fraud is, by definition, the most challenging food control system form because it directly addresses a personal stake benefiting from fraud behavior. In light of the importance of food fraud prevention as an emerging policy, this research aims to answer the question: How is the government of Egypt’s policy working to prevent food fraud, and to what extent is it effective? The study primarily understands food fraud policies in Egypt, explores the current legal and regulatory framework used to deal with food fraud violations in Egypt, and covers the entire food production chain "from farm to fork.” The research also explores the main challenges facing the government to mitigate the problem, the recent and ongoing reforms that the government did to overcome the obstacles, and the new reforms that are happening or need to happen to reduce the problem. A qualitative approach is adopted. Thirteen in-depth interviews were conducted with different food fraud prevention policymakers and implementers from the competent authorities involved. The analysis revealed specific challenges and gaps in the food fraud laws and regulations, food fraud control management system, inspection services, laboratory services, education, and communication. In conclusion, the research introduces a comprehensive set of recommendations that Egypt can apply to strengthen its legal and regulatory framework and improve its policy implementation to fight food fraud in identified areas, including the updating of food fraud laws and regulations, strengthening the food fraud control management system, promoting inspection services, expanding laboratory services, and promoting information, education, and communication.